Pelatihan Pemahaman Fiqih Ubudiyyah pada Peserta Didik di MI Bustanul Ulum Desa Nglele guna Meningkatkan Pemahaman Fiqih Dasar - Muhammad Farid Nasrulloh; Mohammad Saat Ibnu Waqfin; Muhammad Andre Aprilianto; M. Qoyum Zuhriawan; Muhammad Aliyul Wafa; Didin Sirojuddin (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2026)
The sunnah prayer of rawatib is a form of worship that has an important position in Islamic teachings. In the context of education, teaching and fostering students' interest in the sunnah prayer of rawatib among students at the elementary school level. The purpose of implementing community service activities in the Basic Fiqh Understanding Training for Students of MI Bustanul Ulum, Nglele Village, is that students are expected to be able to understand and practice basic ubudiyyah fiqh. The approach method for implementing community service activities in schools under the School Partnership Program scheme includes lectures and discussions. The training on understanding the Ubudiyah Fiqh of Worship at MI Bustanul Ulum, Nglele Village, Sumobito District, Jombang Regency went well and in accordance with the planned objectives. This activity made a positive contribution in increasing students' knowledge, understanding, and skills regarding daily worship practices, especially prayer, thaharah, prayer, and other worship etiquette. Overall, this training is effective as a means of improving the religious competence of MI Bustanul Ulum students, as well as being a real effort in supporting the realization of a generation that is faithful, pious, and has noble character.